THE IMPORTANCE OF LOGICAL CONCEPTS IN MATHEMATICS TEACHING IN SPECIALIZED PRIMARY CLASSES - Muhiddinova Gulzoda Shukur qizi (Web of Journals Publishing, 2024)
This article talks about the role of logical concepts in the teaching of mathematics in specialized primary classes and what needs to be given more importance in this regard.
Keywords: Muhiddinova Gulzoda Shukur qizi